2011
DOI: 10.3952/lithjphys.51202
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity improvement in porous silicon microwave detector

Abstract: Attempts to use microporous silicon structures in detection of microwave radiation were investigated. Point-contact-like samples containing microporous silicon layers were manufactured using traditional technique of electrochemical etching of p-type crystalline silicon. The response of the structures to microwave radiation of 10 GHz frequency was studied. It is shown that the microporous silicon containing samples exhibited sensitivity by several orders higher than that of similar detectors having no porous la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Many preparation techniques have been adopted in synthesizing porous silicon among them is the electrochemical etching technique [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Many preparation techniques have been adopted in synthesizing porous silicon among them is the electrochemical etching technique [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable quantity of interesting works was devoted to create a silicon radiator by means of cheap porous silicon technology [4,5]. A series of recent works was executed on the research of influence of microwave radiation * corresponding author; e-mail: eusat@vgtu.lt on the properties of porous silicon structures [6,7]. It was revealed that the structures had by several orders higher sensitivity to microwave radiation than similar semiconductor structures without a porous layer.…”
Section: Introductionmentioning
confidence: 99%